First- and second-hand consequences of alcohol in college: differential associations with later alcohol use. (2nd January 2016) - Abar, Caitlin C.; Mallett, Kimberly A.; Turrisi, Robert; Abar, Beau
Abstract: Introduction . College students are at increased risk of experiencing a variety of consequences as result of their own as well as others' alcohol consumption. The current study examined the differential associations between both first-hand consequences (resulting from one's own drinking) and second-hand consequences (resulting in victimization as a result of others' drinking) and subsequent alcohol consumption across the first year of college. Method . First year students ( n = 253) from a large northeastern U.S. university were randomly selected to participate and surveyed at the end of the first semester of college (Time 1) and during the first semester of the second year of college (Time 2). Results . Results showed a significant, positive relationship between first-hand consequences and subsequent weekend drinking ( β = 0.16, p < 0.05) and heavy episodic drinking ( β = 0.49, p < 0.01), after controlling for individual and friend drinking. A negative association between second-hand consequences and later heavy episodic drinking was also observed ( β = −0.16, p < 0.05). Discussion and Conclusions . The findings provided partial support for both a positive association hypothesis and a negative association hypothesis. The importance of personal alcohol consumption and peers' drinking in relation to first- and second-hand consequences are discussed.